2019
DOI: 10.1080/14787210.2019.1671823
|View full text |Cite
|
Sign up to set email alerts
|

Pneumocystispneumonia in the twenty-first century: HIV-infected versus HIV-uninfected patients

Abstract: Introduction: Pneumocystis pneumonia (PcP) has classically been described as a serious complication in patients infected with the human immunodeficiency virus (HIV). However, the emerging number of conditions associated with immunosuppression has led to its appearance in other patient populations, such as those receiving chronic corticosteroid therapy, those with hematological or solid malignancies, transplant recipients and those who receive immunomodulatory or biological therapy. Areas covered: This article … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
59
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 116 publications
(128 reference statements)
3
59
0
8
Order By: Relevance
“…One reason for the lower detection rate with microscopic examination was that Wright-Giemsa staining was not performed routinely. The prevalence rates of Pneumocystis pneumonia have been reported ranging from 0 to 11% in non-HIV patients [ 35 ], while the incidence of severe pneumonia caused by P. jirovecii remained undetermined. In this study, P .…”
Section: Discussionmentioning
confidence: 99%
“…One reason for the lower detection rate with microscopic examination was that Wright-Giemsa staining was not performed routinely. The prevalence rates of Pneumocystis pneumonia have been reported ranging from 0 to 11% in non-HIV patients [ 35 ], while the incidence of severe pneumonia caused by P. jirovecii remained undetermined. In this study, P .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found a higher mortality of 2 to 28% in patients with rheumatoid arthritis [30], 13 to 43% in patient with kidney transplant [31], and 30 to 60% in patients with hematological malignancies [23]. According to previous studies, possible prognostic factors in HIV-negative patients were old age, coinfections, respiratory failure, pre-existing lung disease and a higher LDH level [32][33][34]. The reason that no patients died in our study may be due their relatively younger age (average 48.5 years) and the disease itself.…”
Section: Discussionmentioning
confidence: 99%
“…The mortality of HIV-negative PCP patients is estimated to range from 20 to 80%, which is higher than in HIV patients (5-15%) (Rilinger et al, 2019;Shoji et al, 2020). The incidence of PCP in HIV-negative patients has continued to increase in recent years (Cilloniz et al, 2019;Lee et al, 2019), highlighting the need to better understand the immune mechanism against Pneumocystis to identify new therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%